Penerapan Terapi Zikir Terhadap Penurunan Tanda dan Gejala Halusinasi pada Pasien Halusinasi RSJD Dr. RM. Soedjarwadi Provinsi Jawa Tengah - Fionita Putri Mayang Sari; Sitti Rahma Soleman; Wahyu Reknoningsih (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2023)
Hallucinations are one of the symptoms of mental disorders in which the patient experiences changes in sensory perception, feels false sensations in the form of sound or without real stimulation. One way to reduce the impact of auditory hallucinations is by giving dhikr therapy. The objective of the research; To find out the results of the implementation of the Application of Dhikr Therapy on the Level of Signs and Symptoms of Hallucinations in Hallucinatory Patients at Rsjd Dr. Rom. Soedjarwadi, Central Java Province. Method; The research design was conducted on 2 respondents by way of pretest posttest by interviewing and providing observation sheets for signs and symptoms of the ability to control hallucinations. Results; signs and symptoms of the respondent's hallucinations before the dhikr therapy was carried out. Tn.I was at a score of 28 with severe hallucinations and Mr.E was at a score of 26 with severe hallucinations. Then the signs and symptoms of hallucinations after the respondent's dhikr therapy were carried out, Mr. I was at a score of 9 with mild hallucinations and development of signs and symptoms in respondents in controlling auditory hallucinations before and after the dhikr therapy intervention. Summary; There are differences in development before and after dhikr therapy in patients with auditory hallucinations with both respondents having mild hallucinations.